Computer-Aided Discovery of Pentapeptide AEYTR as a Potent Acetylcholinesterase Inhibitor - Enade Perdana Istyastono; Vivitri Dewi Prasasty (Universitas Gadjah Mada, 2021)
One of the key targets in the drug development for potential Alzheimer’s disease (AD) therapeutics is the search for acetylcholinesterase enzyme (AChE) inhibitors. Very recently, a pentapeptide AEYTR was reported as a potential inhibitor for AChE. The peptide was identified in a retrospectively validated virtual screening campaign, which was subsequently followed by 10 ns molecular dynamics (MD) simulations. The study aimed to characterize the structure and identify in vitro of AEYTR peptide as a potent acetylcholinesterase inhibitor. This article presents the structure characterization and the in vitro examination of the peptide as an AChE inhibitor, followed by MD simulations for 100 ns. The results show that the pentapeptide is a potent AChE inhibitor with an IC50 value in the picomolar range and stabilizes the enzyme during MD simulations.